PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE SNOWBALL THROWING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 17 PADANG - Rembaji, Irene; Zulfaneti, Zulfaneti; Husna, Husna (Pendidikan Matematika, 2014)
ABSTRACT This research was designed for revealing whether the mathematic conceptual understanding of the students taught by using Snowball Thorowing active learning model was better than that of students taught by using conventional learning. This was an experimental research. The Population of this research was the students in class IX of SMPN 17 Padang. In collecting the data, an essay post-test that consisted of six items on the conceptual understanding was administered to the sample classes. The data collected was analyzed by using normality test, homogenity test and t-test. Based on the result of data analysis, it was found that the average score of the students in the experrimental class was 83,04 and in the control class was 69,41. This result had indicated that the mathematics conceptual understanding of the students taught by using Snowball Thorowing active learning model was better than that of students taught by using conventional learning in class IX of SM N 17 Padang.